Orthodontic treatment of Class III malocclusion (Case series) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
This article concerns orthodontic treatment of a 20 and 22 years old Bangladeshi female and 23, 21 and 23 years old Bangladeshi male with class III malocclusion. Orthodontic treatment carried out with preadjusted Roth type (018 slot) fixed brackets with maxillary and mandibular anteriors management and alignment to accomplish the treatment. The esthetics and occlusion were maintained after retention. The need for treatment is mainly attributed to esthetic and functional ones. This paper reviews different treatment techniques to manage the situation and presents five cases to illustrate a range of class III malocclusion corrections. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.16000 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 26-27